Safety of Inactivated Influenza Vaccine in Cancer Patients Receiving Immune Checkpoint Inhibitors. (15th March 2019) - Chong, Curtis R; Park, Vivian J; Cohen, Bevin; Postow, Michael A; Wolchok, Jedd D; Kamboj, Mini
Abstract: Background: Cancer patients are at a higher risk for developing influenza (flu)– related complications. It is unclear if the flu vaccine exacerbates immune events in patients treated with immune checkpoint inhibitors (ICIs). Methods: We conducted an institutional review board–IRB-approved retrospective review of advanced cancer patients on ICIs who received the flu vaccine during three 3 consecutive seasons: 2014–2015, 2015–2016, and 2016–2017. The primary outcome assessed was any "new onset" immune-related adverse event (IRAE). A subset analysis of vaccinated patients newly treated with anti–programmed cell death protein 1 (PD-1) agents (nivolumab or pembrolizumab) was conducted to assess overall IRAE rates for comparison with published clinical trials. Results: During the three 3 seasons, 370 patients met criteria for ICI and vaccination within ~ twoapproximately 2 months (65 days). The most common underlying cancers were lung (46%) and melanoma (19%); 61% of patients received an anti–PD-1 agent only. In the entire cohort, 20% experienced an IRAE (any grade); incidence of grade 3 or 4 toxicity was 8%. No grade 5 events occurred. In the subset of 170 patients newly treated with anti–PD-1 agents, the overall IRAE rate was 18% and, grade 3/4 events occurred in 7.6%. Influenza was diagnosed in 2 patients. Conclusions: No increase in incidence or severity of IRAEs was detected in patients on ICIs who received the inactivated influenza vaccine within ~ approximately 2 months of ICI. For newly treated patients on anti–PDI-1 agents, IRAE rates were comparable to those from published clinical trials and did not vary with order of administration. Routine seasonal flu vaccination is encouraged in patients on ICIs. Abstract : For cancer patients who received flu vaccination within 65 days of initiating anti-PD-1 agents, rate of therapy related immune events was comparable to published trials. No severe events occurred after vaccination for all ICIs. Flu vaccine is safe with ICIs.